Association of Triglycerides, HDL, and Waist Circumference with eGFR in patients in private practice (East West Medical College Journal, 2024)
Background: Chronic kidney disease (CKD) is one of the leading causes of mortality and morbidity all over the world. On the other hand, metabolic syndrome has been reported to be associated with adverse renal outcomes. Among the components of metabolic syndrome, diabetes and hypertension are established causes of renal impairment. However, the association of Triglycerides (TGs), High density lipoprotein (HDL), and Waist Circumference (WC) with renal function independently remains understudied. Objectives: The objective of this study was to determine the association of triglycerides, HDL, waist circumference with estimated glomeruar filtration rate (eGFR). Materials and Methods: This cross-sectional study enrolled 100 subjects attending as outpatient in Ibn Sina Diagnostic Centre, Uttara from July 2023 to December 2023. Renal impairment was measured by estimated glomerular filtration rate (eGFR). The eGFR was calculated using the modified modification of diet in renal disease (MDRD) equation. Statistical analyses were performed by using SPSS 25.0 (Statistical Package for Social Science, Inc., Chicago, IL, USA). Continuous variables were expressed as means±standard deviation, and categorical variables as frequencies and proportions. The relationships between renal function with triglycerides, HDL and WC were assessed by correlation coefficient. A p-value